Two Years in the Bosnian Border Area (1479 and 1480) According to Ibn Kemal - Bojanić, Dušanka (Prilozi za orijentalnu filologiju, 2017)
The seventh volume of The History of the Ottoman Dinasty by Ibn Kemal, dedicated to the rule of Mehmed II, contains testimony of contemporaries about Turkish campaign in the south-east Europe in the second half of 15ct. This paper is devoted to the analysis of an abstract from the mentioned volume refering to the Bosnian sangakbey Davud's waging in the border area in 1479 and 1480. Ibn Kemal devoted whole chapters toportraying of the central personality - Davud-paša. Six most interesting chapters have been chosen for this paper and their contents has been compared with available contemporary sources. His descriptions of two famous men, heros of our folk songs, deserve particular attention - descriptions of Vuk Grgurević and Alija Đerzelez. By his way of presenting the protagonists of the described events, Ibn Kemal gave historical characters of these men whose physical and other characteristics agree almost in every detail with those in our folk poetry. Completing our knowledge of such a personality as Đerzelez Alija, he acknowledged the importance of e pic tradition as a historical source.